CASE REPORT ABOUT OVARIAN CISTO IN NEWBORN (CIPEEX, 2022)
FETAL OVARIAN CYSTS, ACCORDING TO THE MOST COMMON ABDOMINAL MASS TYPE, ARE, ACCORDING TO THE MOST ACCEPTED THEORY, CAUSED BY HORMONAL FACTORS. THE AIM OF THE PRESENT STUDY IS TO HIGHLIGHT THE IMPORTANCE OF EARLY DIAGNOSIS AND TREATMENT OF OVARIAN CYSTS IN NEWBORNS. THE REPORT WAS BASED ON THE ANALYSIS OF THE CASE OF A NEWBORN PATIENT WITH A CYST OF 193.0 CM³, EXTENDING FROM THE RIGHT ADNEXIAL REGION SUPERIORLY TO THE HEPATIC SURFACE OF THE RIGHT LOBE, WITHOUT SOLID COMPONENT OR ANOMALOUS CONTRAST ENHANCEMENT . THE DIAGNOSIS IS PREFERABLY MADE BY ULTRASONOGRAPHY, HOWEVER, IT IS ESSENTIAL TO MAKE THE DIFFERENTIAL DIAGNOSIS OF OTHER ABDOMINAL CYSTS. THERE ARE NO GUIDELINES THAT DETERMINE THE TREATMENT IN THESE SITUATIONS, EMPHASIZING THE IMPORTANCE OF THE CLINICAL EVALUATION OF THE PATIENT BY THE HEALTH PROFESSIONAL TO CHOOSE THE MOST APPROPRIATE PROCEDURE, BASED ON THE DATA COLLECTED FINALLY, THE EARLY DIAGNOSIS OF OVARIAN CYST THROUGH THE ULTRASOUND EXAMINATION WOULD FAVOR EARLY TREATMENT, REDUCING THE CONSEQUENCES OF THE OVARIAN CYST, BESIDES CONTRIBUTING TO THE ABSENCE OF SERIOUS COMPLICATIONS AND, CONSEQUENTLY, WORSENING OF THE PROGNOSIS OF THE DISEASE
Keywords: Fetal ovarian cyst, newborn.